Comparison of aerosol optical properties over Lumbini, Pokhara and Langtang-Base Camp - Sapkota, Santosh; Gautam, Sabin; Gautam, Aayush; Poudel, Resham; Pokheral, Santosh; Basent, Kailash; Subedi, Aabiskar (Himalayan Physics, 2023)
The comparative study of aerosol optical properties at different tourist places in Nepal has been performed. Lumbini, Pokhara and Langtang-Base Camp (BC) were the places chosen for observation. Aerosols are made up of a variety of airborne particles both fine and coarse and are most prevalent in urban industrial Areas. The data was collected from AERONET websites between 2017 and 2019 for each of the locations. The ranges of AOD over Pokhara and Langtang-BC were discovered to be lower (0.1 and 0.01) and the maximum and minimum values of AOD (675 nm) in Lumbini occurred predominantly in winter and summer monsoon respectively. The causes of the highest AOD levels were land clearing for crop cultivation and vegetation fires which were then followed by biomass burning for heating purposes and pollution from brick kilns, industry and vehicles. AOD, angstrom exponent (α and β) and Visibility are distinct from typical seasonal variations. The total AE fluctuations show that a combination of fine and coarse mode particles as well as anthropogenic aerosols made up the majority of the aerosol loading during the research period. Visibility was inversely related to the turbidity coefficient (β). Three times as much visibility was discovered over Langtang-BC as compared to Lumbini and Pokhara. Over these three locations, precipitable water peaked in the summer and dropped in the winter. These three sites seasonal changes are found to be distinct for each parameter.